New Precast Bridge Girder with Combined Prestressing - Moravcik, Martin; Bujnakova, Petra (Communications - Scientific letters of the University of Zilina, 2011)
Traditionally, the major part of highway bridges in Slovakia is realized using the precast concrete technology. The common Slovak precast girders are produced to the34 m length as one element. Nowadays, there is an increasing demand for more economical and resisting bridge structures with longer spans. The company Vahostav-Sk-PREFA, Ltd as the main supplier of precast elements for highwaybridge 207, in cooperation with theUniversity of Zilina and the designer company Dopravoprojekt Inc. Liptovsky Mikulas, developed a new precast girder MDP for the span 38 m with combined prestressing. Some experiences and results of verifying flexural test with numerical analysis of that girder are presented in this paper.